A comprehensive expression analysis of the MIA gene family in malignancies: MIA gene family members are novel, useful markers of esophageal, lung, and cervical squamous cell carcinoma - Sasahira, Tomonori; Kirita, Tadaaki; Nishiguchi, Yukiko; Kurihara, Miyako; Nakashima, Chie; Boßerhoff, Anja Katrin; Kuniyasu, Hiroki (Oncotarget, 2016)
Melanoma inhibitory activity (MIA) gene family members include MIA, MIA2, and Transport and Golgi organization protein 1 (TANGO). Although MIA gene family members have several tumor-related functions, their detailed roles in malignancies remain poorly elucidated. In this study, 477 tumor specimens were subjected to immunohistochemical screening to evaluate MIA gene family expression. For a validation analysis, we also examined the association between MIA gene family expression and clinicopathological factors in 66 cases of esophageal cancer, 145 cases of lung cancer, and 126 cases of cervical cancer. The frequency of MIA gene family expression was higher among squamous cell carcinomas than among other tumor types subjected to screening. In the validation analysis, MIA gene family staining was observed frequently in esophageal and lung cancers associated with nodal and/or distant metastasis. In cervical cancers, MIA and TANGO immunostaining also correlated with tumor progression and metastasis. Furthermore, MIA2 expression levels in invasive cervical cancer were upregulated relative to those in cervical intraepithelial neoplasia 3. A disease-free survival analysis revealed that MIA-, MIA2, or TANGO-positive patients had a significantly shorter disease-free survival than did those patients who were negative. Our results suggest that MIA, MIA2, and TANGO may be useful diagnostic and therapeutic molecular targets in human malignancies.
EVALuna2:4728